Optimization of Counseling by the Binmas Unit to Prevent Breaking and Entering Theft in the Jurisdiction of Temanggung Police - Mubarok, Azwin (Advances in Police Science Research Journal, 2024)
The author raises the final task with the title "Optimization of Counseling Guidance by the Binmas Unit to Prevent Theft by Weighting in the Legal Area of the Temanggung Police". This writing aims to optimize counseling guidance by the Binmas Unit of the Temanggung Police in preventing acts of theft by weighting in the jurisdiction of the Temanggung Police. The research method used in this writing is a qualitative approach using data collection techniques through document studies, interviews and observation. This study uses management theory, organizational resource theory and SWOT theory as well as several concepts that support the implementation of the research, namely the optimization concept, the counseling guidance concept, the Binmas Unit concept, the crime prevention concept and the Temanggung area concept. The results of the study indicate that the extension guidance carried out by the Binmas Unit of the Temanggung Police still needs to be optimized. This is due to a discrepancy between factual conditions in the field and expected conditions. this is indicated by the existence of deficiencies found in the Binmas Unit in conducting extension guidance, both in terms of its organizational resources and its implementation management system. To overcome these deficiencies, several problem solving related to factual conditions that do not match the expected conditions have been made by adjusting existing regulations.